Accounting for Undergraduates’ Teaching Perspectives in a Scholarly Teaching Encounter - Pitso, Teboho; Lebusa, Malefane; Kok, Lawrence (South African Journal of Higher Education, 2018)
Students’ feedback has mostly involved face-to-face or online questionnaires administered by agencies outside actual classroom experiences. Increasingly, students’ feedback forms part of scholarly focus on teaching and is organized as part of improving students’ learning. This marks a shift from using students’ feedback as a satisfaction measuring tool similar to customer satisfaction surveys or as mechanisms to measure teachers’ performance (a quality-oriented perspective). In scholarly teaching, students’ feedback forms part of a larger inquiry into the teacher’s practices. It involves students’ reaction to teaching and teacher’s reaction to students’ feedback guided by societal trends and the need to improve students’ learning. We report, in this article, on the exploratory study that focused on guided self-study inquiry into one teacher’s practices guided by changing workplace dynamics. Through focus group interviews, final-year Labour Relations students’ experiences of teaching were elicited and factored into the developing scholarly teaching mechanism aimed at improving learning.